Comparison of Conservative versus Surgical Treatment Protocols in Treating Idiopathic Granulomatous Mastitis: A Meta-Analysis - Zhou, Fei (Breast Care (Basel), 2020)
BACKGROUND: Idiopathic granulomatous mastitis (IGM) is a rare, benign breast disease without any definitive therapeutic strategy. It is controversial whether to use conservative or surgical treatment of IGM and high-level evidence-based medicine data are lacking. The purpose of this study was to systemically evaluate the clinical effectiveness of the conservative versus surgical treatment for IGM. METHODS: In this meta-analysis, we searched PubMed, EMbase, ScienceDirect, and Web of Science for comparative studies about the conservative versus surgical treatment of IGM. Two researchers independently identified reports and extracted data. We used Stata 11 for data analysis. A meta-analysis was performed to investigate the differences in the recurrence rate of conservative and surgical treatment using a random effects model. RESULTS: A total of 10 studies involving 1,101 patients were included. The results demonstrated that there was no significant difference in the recurrence rate among patients who were treated by nonsurgical therapy and surgical treatment. No publication bias was detected. CONCLUSION: This meta-analysis demonstrates that both the conservative and surgical treatment approaches have appropriate efficacy in IGM treatment and relapse. Further randomized controlled trials with longer follow-up periods are required to confirm the advantages of each approach.